Study on the Application of Tolerance and Religious Harmony in Primary School - Reza, Muhammad; Naufal, Naufal; Yamin, Muhammad (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Indonesia is a country with a high diversity of religions and local beliefs, making tolerance an absolute requirement for maintaining social stability from ideological and physical conflict. However, the challenges of modernization often test how these values ​​of tolerance are internalized by the younger generation amidst the free flow of information. This study aims to analyze the perspectives and understanding of the millennial generation regarding the practice of interfaith tolerance in everyday life. This study uses a descriptive qualitative approach. Data was collected through field observations and in-depth interviews with millennial respondents. Data analysis techniques were carried out using the Miles and Hubberman model, which includes data reduction, data presentation (data display), and verification or drawing conclusions. The findings indicate that millennials have a very positive and open view of interfaith harmony. Respondents tend to separate theological domains from social interactions, where they consider religion as an individual's right to privacy that should not hinder social cooperation. They are not affected by differences in belief in building professional or personal relationships. Practically, this study provides policymakers and educational institutions with an understanding that the narrative of religious moderation has been well-received by millennials, which can become important social capital in maintaining national integration in the future.